2017
DOI: 10.5433/1679-0359.2017v38n5p3069
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary supplementation with omega-3 and -6 on fresh and frozen/thawed sperm quality of dogs

Abstract: For years, fatty acids have been recommended as a dietary supplement to improve canine hair. For animal reproduction, supplementation with omegas has been used to increase the reproductive efficiency and conception rate, but few studies have been conducted in dogs. The aim of this study was to evaluate the effects of daily dietary supplementation with omega-3 and -6 on the quality of fresh and frozen/ thawed semen in canines. Semen was collected from seven dogs and evaluated for sperm motility, vigor, concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Omega-3 and Omega-6 are essential components of the plasma membrane of spermatozoa and when supplied through nutraceuticals increase membrane stability and allow spermatozoa to withstand the physical stress caused by cooling and freezing (Rodrigues et al, 2017). The present study showed that the addition of DHPG to the extender reduced DNA damage and improved plasma membrane integrity in canine semen following thawing.…”
Section: F I G U R Esupporting
confidence: 52%
See 1 more Smart Citation
“…Omega-3 and Omega-6 are essential components of the plasma membrane of spermatozoa and when supplied through nutraceuticals increase membrane stability and allow spermatozoa to withstand the physical stress caused by cooling and freezing (Rodrigues et al, 2017). The present study showed that the addition of DHPG to the extender reduced DNA damage and improved plasma membrane integrity in canine semen following thawing.…”
Section: F I G U R Esupporting
confidence: 52%
“…Polyunsaturated fatty acids are components of seminal plasma, are present in the membranes of sperm, and influence the fluidity of the membrane, motility and capacitation in sperm (Placer et al., 1966; Retterstol et al., 2001; Zeron et al., 2002). Omega‐3 and Omega‐6 are essential components of the plasma membrane of spermatozoa and when supplied through nutraceuticals increase membrane stability and allow spermatozoa to withstand the physical stress caused by cooling and freezing (Rodrigues et al., 2017). The present study showed that the addition of DHPG to the extender reduced DNA damage and improved plasma membrane integrity in canine semen following thawing.…”
Section: Discussionmentioning
confidence: 99%
“…Various researchers have used different periods of supplementation with PUFAs, such as 60 days (stallions), 16 weeks (boars), 30 weeks (stallions) and 174 days (boars) (Freitas et al, ; Lin et al, ; Liu et al, ; Rodrigues et al, ). We believe our experiment is the first assessing the possible alterations at 60 days after the end of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…could enhance sperm quality in dogs. Although the effects of many dietary supplements on dog sperm have been evaluated before ( 26 28 ), probiotics effects have not been evaluated yet. We selected three commensal Lactobacillus spp., namely Lactobacillus acidophilus, Limosilactobacillus reuteri (previously known as Lactobacillus reuteri ), and Ligilactobacillus salivarius ( Lactobacillus salivarius ), based on our previous study ( 21 ).…”
Section: Introductionmentioning
confidence: 99%